Only in Congenial Soil: The Microenvironment in Brain Tumorigenesis - Rubin, Joshua B. (Brain Pathol, 2008)
Microenvironmental or stromal influences on tumor formation and growth have become an active area of research. The use of mouse models of human cancers to study the role of the microenvironment will yield unique insights into this aspect of tumor biology and should identify novel therapeutic targets for the treatment of human cancers. In the following, the author review the natural history of two pediatric brain tumors, optic pathway glioma in neurofibromatosis type 1 and medulloblastoma in Gorlin's Syndrome, whose patterns of growth suggest that microenvironmental factors are essential for tumor formation. Each of these brain tumors is faithfully modeled in genetically engineered mice and the use of these mouse models to investigate the role of the microenvironment should yield exciting new insights into this important field of study.